1975
DOI: 10.1002/bbpc.19750790608
|View full text |Cite
|
Sign up to set email alerts
|

The Quantum Yield of Photolysis of Water on TiO2 Electrodes

Abstract: The qu;intuni yield of the photo-currents in the electrochemical cell. n-TiO,jelectrolyte/Pt, was measured under monochromatic illumination of TiO, at various electrode potentials, It has been found that the quantum yield is very small ( -10- ') in case where no voltage was applied from outside, getting smaller with illumination intensity. The results of measurements of the quantum yield. together with those of the electrode potential of T i 0 2 . at various conditions are explained from the energy level sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
2

Year Published

1976
1976
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 7 publications
2
47
2
Order By: Relevance
“…The rising position of cathodic current due to H 2 generation shifts to negative potential with an increase in pH. The position of flat-band potential is shown as fb by using the Nernst equation of Àð0:177 þ 0:059 Â pHÞ (V) vs Ag/AgCl for rutile-rich TiO 2 reported by Ohnishi et al 8) To compare the flat-band potential and the rising position of cathodic current, it is shown that negative overvoltage is necessary to induce the cathodic current and H 2 generation. The electron injection from the TiO 2 electrode to the reduction potential of H þ (aq) is realized by negative voltage over the flat-band potential, which produces downward band bending in TiO 2 .…”
mentioning
confidence: 98%
“…The rising position of cathodic current due to H 2 generation shifts to negative potential with an increase in pH. The position of flat-band potential is shown as fb by using the Nernst equation of Àð0:177 þ 0:059 Â pHÞ (V) vs Ag/AgCl for rutile-rich TiO 2 reported by Ohnishi et al 8) To compare the flat-band potential and the rising position of cathodic current, it is shown that negative overvoltage is necessary to induce the cathodic current and H 2 generation. The electron injection from the TiO 2 electrode to the reduction potential of H þ (aq) is realized by negative voltage over the flat-band potential, which produces downward band bending in TiO 2 .…”
mentioning
confidence: 98%
“…At a disk potential of 1V vs. SCE used here, the disk current saturated. The quantum yield of the photocurrents in the electrochemical cell, n-TiOdelectrolyte/Pt was found to be -0.6 (20). A photon flux of 1014 cm -2 s -1 yielded a saturated disk current of -10 p.A/cm 2.…”
Section: Resultsmentioning
confidence: 95%
“…Work by other groups to reproduce the discovery established the conditions necessary for sustainable, spontaneous water splitting. [21][22][23][24][25][26] Fujishima and Honda's report ignited considerable interest in exploring solar water splitting as a practical means to generate clean fuels and led to efforts to find other semiconductor materials that could yield higher efficiencies. Much of the subsequent work focused on wide-band gap metal oxides and oxynitrides, whose valence and conduction band positions ''straddle'' the water splitting redox potentials.…”
Section: History Of Solar-driven Photoelectrochemical (Pec) Water Splmentioning
confidence: 99%